Preclinical development of gastro-protective botanical candidate from Woodfordia fruticosa (Linn.) Kurz: Chemical standardization, efficacy, pharmacokinetics and safety pharmacology. (15th September 2019) - Khan, Inshad A.; Singh, Amarinder; Mindala, Durga P.; Meena, Samdarshi; Vij, Bhavana; Yadav, Arvind K.; Roy, Sumit; Nandi, Utpal; Katare, Anil K.; Jaglan, Sundeep; Singh, Deepika; Gupta, Ajai P.; et al.
Abstract: Ethnopharmacological relevance: Woodfordia fruticosa is traditionally used in the Ayurvedic system of medicine for the treatment of diarrhoea, poisoning, menstrual disorders, ulcers and fertility. In the present study, we report a standardized extract preparation through modern scientific approach for anti-ulcer activity. Materials and methods: The hydro-alcoholic extract of flowers of W. fruticosa was standardized using four chemical markers. The standardized extract was coded as ICB014. HPLC method was developed for identification and quantification of Gallic Acid, Oenothein-C, Quercetin and Kaempferol. Based on the prior published H +, K + -ATPase activity and Anti-bacterial activity against Helicobacter pylori of ICB014, was evaluated for its in-vivo efficacy in gastric ulcers models in rats followed by regulatory safety studies. Results: The extract demonstrated efficacy at 31.25–62.5 mg/kg in gastric ulcer models. The extract was safe by oral route up to 2000 mg/kg in a single dose and NOAEL of 800 mg/kg in 28 days repeat study. Bioequivalent capsule formulation was prepared. Conclusions: The extract showed anti-ulcer potential and is ready for clinical evaluation. Graphical abstract: Image 1